Activation of Siglec-7 results in inhibition of in vitro and in vivo growth of human mast cell leukemia cells. (August 2020) - Landolina, Nadine; Zaffran, Ilan; Smiljkovic, Dubravka; Serrano-Candelas, Eva; Schmiedel, Dominik; Friedman, Sheli; Arock, Michel; Hartmann, Karin; Pikarsky, Eli; Mandelboim, Ofer; Martin, Margarita; Valent, Peter; et al.
Graphical abstract: Abstract: Advanced systemic mastocytosis is a rare and still untreatable disease. Blocking antibodies against inhibitory receptors, also known as "immune checkpoints", have revolutionized anti-cancer treatment. Inhibitory receptors are expressed not only on normal immune cells, including mast cells but also on neoplastic cells. Whether activation of inhibitory receptors through monoclonal antibodies can lead to tumor growth inhibition remains mostly unknown. Here we show that the inhibitory receptor Siglec-7 is expressed by primary neoplastic mast cells in patients with systemic mastocytosis and by mast cell leukemia cell lines. Activation of Siglec-7 by anti-Siglec-7 monoclonal antibody caused phosphorylation of Src homology region 2 domain-containing phosphatase-1 (SHP-1), reduced phosphorylation of KIT and induced growth inhibition in mast cell lines. In SCID-beige mice injected with either the human mast cell line HMC-1.1 and HMC-1.2 or with Siglec-7 transduced B cell lymphoma cells, anti-Siglec-7 monoclonal antibody reduced tumor growth by a mechanism involving Siglec-7 cytoplasmic domains in "preventive" and "treatment" settings. These data demonstrate that activation of Siglec-7 on mast cell lines can inhibit their growth in vitro and in vivo . This might pave the way to additional treatment strategies for mastocytosis.